Formulation development, characterization, and evaluation of sorafenib-loaded PLGA–chitosan nanoparticles - Mateen, Abdul; Khan, Abad; Khan, Ismail; Ahmad, Lateef; Khan, Amjad; Salam, Abdul (Frontiers in Pharmacology, 2024)
The basic purpose of this work was to develop environmental friendly, biodegradable and biocompatible polymeric nanoparticles of sorafenib, which can effectively release the desired drug in a customized and controlled manner for targeting hepatocellular carcinoma. Solvent evaporation technique was employed for the synthesis of Sorafenib loaded PLGA-Chitosan nanoparticles followed by various experimental specifications and compatibility studies using poloxamer 407 as stabilizer. The best nanoparticles thus synthesized were selected to be used for cytotoxicity investigations, in vitro and in vivo assessments. For the in vitro drug release tests, the dialysis bag diffusion technique was used. For both chitosan nanoparticles and PLGA loaded with sorafenib, a biphasic release pattern was found, exhibiting a protracted release lasting 10 days after a 24-hour burst release. As experimental animals, rabbits were utilized to evaluate different in-vivo pharmacokinetic properties of selected formulations. Plasma samples were extracted with acetonitrile and analyzed through the developed HPLC method. The pharmacokinetic parameters such as AUC 0-t , C max MRT, Vd, and half-life (t 1/2 ), were enhanced significantly (p ≤ 0.001), while clearance has considerably diminished (p ≤ 0.001) regarding the chosen synthesized nanoparticles in contrast to commercially accessible sorafenib formulation (Nexavar®). The reference drug's cytotoxicity and sorafenib loaded PLGA and chitosan nanoparticles were calculated by performing MTT assay against HepG2 cell lines. The developed polymeric sorafenib nanoformulations possess the appropriate physiochemical properties, better targeting, surface morphology, and prolonged release kinetics. The pharmacokinetic parameters were improved significantly when results were compared with commercially available sorafenib formulations.